Sistem Penentu Calon Penerima Beasiswa Menggunakan Metode Smarter dan Forward Chaining - Fadly Fadly; Yulia Darmi; Dedy A Prabowo (UNIVED Press, 2017)
This research aims to create a program to help facilitate the school in determining the students who are eligible for a scholarship. SMA Muhammadiyah 4 Kota Bengkulu serve as research place. The selection process of scholarship recipients in SMA Muhammadiyah 4 Kota Bengkulu is equipped with various criteria, such as family economy, family dependent, child status, School Achievement, out-of-school education and discipline. It should be noted in the assessment of the criteria and must be relevant because it will basically affect the outcome. In making this Program we use Visual Basic 6.0 software and apply SMARTER Inference Forward Chaining method. The results obtained from this study, have met the criteria desired by the SMA Muhammadiyah 4 Kota Bengkulu and the use of this method is considered effective to be used to anticipate the similarity of the ranking. So that the selection process of scholarship recipients in SMA Muhammadiyah 4 Bengkulu City on target.Keyword : Decision support system, Simple Multi-Atribute Rating Technique Exploiting Rank (SMARTER), Forward Chaining